A arte como instrumento de trabalho da(o) assistente social - Santos, Franciele Machado dos (2019)
The purpose of this dissertation is to study the use of art as a working tool for social workers. The objective is to know how these professionals mediate art as an intervention tool in the daily work and if this mediation contributes to the materialization of the Ethical-Political Project of Social Service. The introduction brings initial approximations with the discussions about artistic production, potentialities of its use as instrument, as well as presents the methodological paths of the research. It characterizes the method of investigation and the method of exposition in Marx and the dialectic categories that compose it. The first chapters of theoretical construction have as centrality the work category, contributing reflections on the Marxian conception of work and work process, problematizing the work of the social worker and finally the mediation and the possibilities of mediation of the art in the accomplishment of this specialization of the job. The method that guided the study was the dialectical, materialist and historical, based on the epistemological categories: totality, historicity, contradiction and mediation, plus the ontological ones: work, art, instrumental and daily life, to answer the following research problem: In what way the art is used as a work tool of the Social Assistants that intervene in different socio-occupational spaces of the public sphere in the city of Porto Alegre? The research was characterized as mixed type, considering quantitative and qualitative data, with emphasis on the latter. For data collection, an online questionnaire was used for the preliminary survey on the use of art at work and the type of art most used. This cut was of the transversal type and counted with the participation of eighty-one (81) respondent subjects with training in Social Work. Subsequently, interviews were conducted for further study. The people who participated in the research were six (6) social workers, five (5) women and one (1) man, who work in Porto Alegre. The main results show the contradiction, since many professionals are aware of the potentialities of the use of art as a work tool, but when using it as part of the instrumental shift the developed actions of the theoretical-methodological and ethical-political knowledge of the profession. In this sense, they make a technocratic use of art due to theoretical fragility. Added to the difficulty of appropriation of the fundamentals and critical theory that subsidizes the Social Service processes of precarious working conditions and, consequently, deepening alienation. However, even with these difficulties, how professionals can use art as part of the work, and contribute to the strengthening of art, through the expansion of knowledge, information as a right and the possibility of accessing rights, How to subsidize criticism and new perspectives, boosting the process of building a less unequal society.